Illegal Walleye introduction may destabilize a wild Lake Trout—Cutthroat Trout fishery in a Wyoming reservoir - Johnson, Clark F., author; Johnson, Brett M., advisor; Klein, Julia, committee member; Myrick, Christopher, committee member (Colorado State University. Libraries, 2016)
Introduced Lake Trout Salvelinus namaycush coexisted for decades with wild, native Yellowstone Cutthroat Trout Oncorhynchus clarkii bouvieri and Rainbow Trout O. mykiss in Buffalo Bill Reservoir, Wyoming. Recently, managers became concerned when illegally introduced Walleye Sander vitreus were discovered. The goals of this study were to examine potential habitat constraints on predator-prey interactions, and determine how arrival of a coolwater predator may affect the Oncorhynchus population. We measured limnological variables and used gill nets, electrofishing and trap nets to sample fish populations monthly during April–October in 2012 and 2013 to determine fish habitat use and collect samples for growth and diet analyses. Prior to thermal stratification Lake Trout, Oncorhynchus spp., and Walleye co-occurred at depths <18 m, but during summer Walleye and Oncorhynchus spp. remained in shallow water and Lake Trout retreated to the hypolimnion. Only large (≥ 600 mm TL) Lake Trout consumed Oncorhynchus spp. and only during the unstratified period, but 64% of diet of all Walleye sampled was Oncorhynchus spp. regardless of stratification. Low Secchi depth (mean = 1.6 m) and warm (19°C) epilimnetic temperatures appear to have inhibited Lake Trout predation on Oncorhynchus spp. in summer and made conditions more favorable for Walleye. Abundance estimation showed that Lake Trout abundance (17,894 fish > 210 mm TL, 68% CI = 13,765–22,531) was lower than Oncorhynchus spp. (43,872 fish, 90% CI = 33,627–54,118). Walleye appeared to still be rare and could not be enumerated with confidence. Bioenergetics modeling showed that lifetime per capita consumption of Oncorhynchus spp. by Lake Trout (18.29 kg) was similar to that by Walleye (14.71 kg), despite the longer lifespan of Lake Trout. A growing Walleye population may adversely affect both Lake Trout and Oncorhynchus populations in this system.